INCLUSIVE LITERACY: A REVIEW OF LIBRARY ROLES IN SUPPORTING INFORMATION LITERACY DEVELOPMENT FOR STUDENTS WITH SPECIAL NEEDS - Asma Nadia Zanol Rashid; Mohd Shamsul Daud; Nur Areena Aqilah Mohd Sapri; Wan Ainol Mursyida Ahmad Tarmizi; Noor Syakinah Mohd Ridwan; Tayyib Idrisa Kadi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This article discusses the issue of how libraries can assist students with disabilities in developing their information literacy skills effectively and efficiently. This review aims to examine and combine studies on library methods, approaches, and materials designed to promote information literacy in this overlooked demographic. A comprehensive examination of research underscores the role that libraries play in improving literacy capabilities and ensuring fair access to information; nonetheless, there are notable deficiencies in tailored approaches and the effectiveness of these programs in supporting students with unique requirements. Results from studies show that although numerous libraries embrace methods, there's a noticeable lack of thorough frameworks and cooperative strategies that blend technology with teaching methods. The research highlights the significance of teamwork involving librarians, educators and tech experts to devise resources and initiatives. Furthermore, the study stresses the need for establishing guidelines that support inclusion in library services. The findings of this study have ranging effects. Indicate that libraries need to broaden their grasp of accessibility and take proactive steps to build welcoming environments that cater to everyone's needs effectively through collaborations and creative approaches. By doing libraries can improve their support, for students with requirements which can boost their ability to na. PG: 558_570vigate information and contribute to academic achievements overall. This research also highlights the need for more studies in this area, calling for a framework that enables all students to develop information literacy skills.